Health and fitness of young, healthy adult females and the effect of an eight week pilates intervention - Eaton, Lara Lee (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
Purpose: The first phase of this study aimed to investigate the health and fitness status of young adult females in the local community. The second phase of this study investigated the impact of an eight week progressive Pilates intervention on selected health and fitness parameters in this cohort. Methods: Healthy young adult females aged 18-26 years (n=96), from the local community, partook in once-off tests including anthropometric measures (stature, body mass, Body Mass Index and waist circumference) as well as fitness parameters including balance, flexibility, muscular strength and endurance, and lastly lumbo-pelvic stability. Health measures investigated included blood pressure and spirometry. Where possible, results were compared to those of similar populations from national surveys or published normative data. Sedentary volunteers from this cohort were then randomised into a Pilates Exercise (PEx, n=12) or an inactive Control (Con, n=11) group, with their results from Phase 1 serving as baseline measures. Pilates classes were held twice weekly (60 minutes per session). All the measures from phase 1 were repeated at weeks 4 and 8. An additional intervention test included Transversus abdominis recruitment. Participants maintained habitual dietary intake and energy expenditure throughout. Nine PEx group and eight Con group participants completed the intervention. Results: The current sample (phase 1) was found to be healthier than comparative populations from national surveys, and significant differences (p<0.05) were found for all comparisons except Forced Expiratory Volume (FEV1), (p=0.64). Physical activity levels (230 min.week-1) exceeded that of the recommend weekly threshold (150 min.week-1). BMI, waist circumference, blood pressure and spirometry measures were all found to be within suggested healthy normal ranges. Pilates significantly improved lumbo-pelvic stability in the PEx group at weeks 4 (p<0.005) and 8 (p<0.002). Similarly, abdominal (p=0.00, d=1.1), upper limb (p=0.037, d=0.9) and lower limb endurance (p=0.02, d=1.0, between group d=0.73 for PEx) also improved with no changes in the Con group. PEx energy expenditure significantly increased from baseline to weeks 4 (p=0.007, d=10.7) and 8 (p=0.027, d=0.64), however body mass was maintained throughout. Conversely, Minute Ventilation decreased in the PEx cohort (p=0.010, d=0.95) from weeks 4 to 8. The Con group showed significant increases in body mass (p=0.018), leg strength (within-group Cohen's d=-1.08 between weeks 0-8; d=-2 between weeks 4-8) and dynamic balance (p=0.01, d=-0.5). While no within-group changes were observed, Protein intake was significantly greater (p=0.036, d>0.8 at baseline and week 8) in the PEx group throughout the intervention. Medium between-group effect sizes (d>0.5) were noted for PEx BMI and waist circumference measures at all time points. Further, although not significant, the large within-group effect size (d=-0.84) between baseline and week 8 for PEx systolic blood pressure, suggested the 9 mm Hg was meaningful. The same time period also indicated a large within-group effect size (d=-0.8) for PEx dynamic balance, and a medium Cohen's d for (d=0.57) PEx static balance. Conclusion: The local population of young adult females was found to be significantly healthier than those of comparable national samples. Further, Pilates participation significantly improved lumbo-pelvic stability and muscular endurance with meaningful changes in systolic blood pressure, and balance in previously sedentary young, adult females. Body mass was also maintained.
Keywords: Physical fitness for women -- South Africa -- Makhanda; Pilates method; Exercise for women -- South Africa -- Makhanda; Exercise -- Health aspects -- South Africa -- Makhanda; Exercise -- Physiological aspects -- South Africa -- Makhanda